Endoscopic balloon dilatation is an effective management strategy for caustic-induced gastric outlet obstruction: a 15-year single center experience - Kochhar, Rakesh; Malik, Sarthak; Reddy, Yalaka Rami; Mallick, Bipadabhanjan; Dhaka, Narendra; Gupta, Pankaj; Sinha, Saroj Kant; Manrai, Manish; Kochhar, Suman; Wig, Jai D.; Gupta, Vikas (Endoscopy International Open, 2019)
Background and study aims There is sparse data on the endoscopic management of caustic-induced gastric outlet obstruction (GOO). The present retrospective study aimed to define the response to endoscopic balloon dilatation (EBD) in such patients and their long-term outcome.Patients and methods The data from symptomatic patients of caustic-induced GOO who underwent EBD at our tertiary care center between January 1999 and June 2014 were retrieved. EBD was performed using wire-guided balloons in an incremental manner. Procedural success and clinical success of EBD were evaluated, including complications and long-term outcome.Results A total of 138 patients were evaluated of whom 111 underwent EBD (mean age: 30.79 ± 11.95 years; 65 male patients; 78 patients with isolated gastric stricture; 33 patients with both esophagus plus gastric stricture). The initial balloon diameter at the start of dilatation, and the last balloon diameter were 9.6 ± 2.06 mm (6 – 15 mm) and 14.5 ± 1.6 mm (6 – 15 mm), respectively. Procedural and clinical success was achieved in 95 (85.6 %) and 108 (97.3 %) patients, respectively, requiring a mean (SD) of 5.3 (2.6) and 7.21 (3.86) sessions, respectively. Patients with isolated gastric obstruction had a better response than those with combined esophagus and gastric stricture. Minor complications such as self-limited pain or bleeding were seen in 18 (16.2 %) and 16 (14.4 %), respectively. Perforation occurred in two patients. Over a follow-up period of 98 months, there were no recurrences.Conclusion Caustic-induced GOO can be successfully managed using EBD with 97.3 % clinical success.